HUBUNGAN FAKTOR RISIKO KEJADIAN UNMET NEED KB (KELUARGA BERENCANA) DI DESA ADIWERNA, KECAMATAN ADIWERNA, KABUPATEN TEGAL, TRIWULAN III TAHUN 2016 - Khaerunnisa Uljanah; Sri Winarni; Atik Mawarni (Jurnal Kesehatan Masyarakat (Undip), 2016)
Unmet need for family planning is the need for family planning to reproductive age couples but such a need (not want any more children or want to space their next pregnancy) is not met and do not use contraceptives of any kind. Unmet need in the village Adiwerna quite high at 23.54%, very far from the national target of 6.5%. This study aimed to analyze the relationship between risk factors and the incidence of unmet need for family planning. This type of research is explanatory research with case control study design. The population in this study were 1,500 women (reproductive age couples). A large sample of 102 selected by simple random sampling. The analysis was performed with chi square test with continuity correction method. The results showed there is a significant risk factor 4 with an unmet need in the village Adiwerna the age group (p-value = 0.009; OR = 3.614; 95% CI = 1.396 to 7.172), the number of children living (p-value = 0.050; OR = 2.645 ; 95% CI = 1.085 to 6.448), the support of her husband (p-value = 0.001; OR = 9.886; 95% CI = 3.579 to 27.313), and social support (p-value = 0.023; OR = 2.889; 95% CI = 1.236 to 6.753). And there are seven variables were not significant: education (p-value = 0.529), income (p-value = 1.000), husband's work (p-value = 1.000), side effects (p-value = 0.415), knowledge (p- value = 0.552), attitude (p-value = 0.322), and religious prohibitions (p-value = 0.404). IEC for family planning need their husbands and for acceptors include childbearing years old, it is advisable to use sterile contraception for those who already do not want more children.